Using the Accelerating Rate Calorimetry for Determination of Energetic Materials Thermal Hazards - Mašín, Jindřich; Šelešovský, Jakub; Ferjenčík, Miloš (Česká společnost průmyslové chemie, 2016)
The thermal hazard is a cause of many serious industrial accidents, typically represented by runaway reactions. The key to prevention of these accidents is to comprehend a complex behaviour of substances with the runaway potential. Classic theories of thermal explosion are capable to describe the problem of thermal runaway reaction. However these theories are difficult to be daily used. For the practical purposes of the industrial safety a different approach is possible. For the safety of a process where thermal hazard could exert, four temperatures must be known: adiabatic temperature rise, decomposition temperature, standard temperature of a process and boiling point of a reaction mixture. From the relation among these parameters the processes can be then divided into several classes of hazard level. Standard temperature of the process is given by technology; the boiling point of the reaction mixture is given by its composition. The determination of decomposition temperature and adiabatic temperature rise is a complex problem. Usually thermoanalytical methods are used to obtain these parameters. One of the suitable methods is accelerating rate calorimetry (ARC). Using of ARC to determine the decomposition temperature and the adiabatic temperature rise is a main topic of this article. Compared to other thermoanalytical methods, ARC provides quite unique experimental conditions. The relatively large amount of the sample is used; pressure above the decomposing sample is monitored. The calorimeter simulates adiabatic decomposition of the sample. The decomposition of dibenzoyl peroxide solution and pentrite (pentaerythritol tetranitrate) was studied with ARC. The determination of the adiabatic temperature rise, the decomposition temperature and the influence of a sample and bomb masses and concentration on both parameters are discussed.
Používání kalorimetrie ARC pro určování tepelných zdrojů rizika energetických materiálů
Keywords: major accident; safety management system; risk assessment; závažná havárie; systém řízení bezpečnosti; hodnocení rizika